Pengaruh Penggunaan Media Podcast dan Media Video Terhadap Peningkatan Pengetahuan Pedoman Gizi Seimbang Pada Remaja - Assabila, Sarah Yuliani; Kurniasari, Ratih (JURNAL RISET GIZI, 2022)
Background: The level of nutritional knowledge among adolescents is one of the factors that influence their food choices. Lack of knowledge in adolescents about balanced nutrition allows them to choose foods that tend to be unhealthy and less nutritious and result in unstable weight gain or loss.Objective : This study aims to determine the differences in the effect of nutrition education on general guidelines for balanced nutrition using Podcast media through the Spotify platform and video media on adolescents.Methods : This type of research is a quasi-experiment with pre and post-test with two group designs. The number of samples was 30 students of grade eight in Junior High School. The sampling technique used purposive sampling. Analysis of data using the Wilcoxon and Mann Whitney tests.Results : The results showed the highest increase in the mean score of general guidelines for balanced nutrition knowledge (12.67 ± 1.58) and were significant in the group given Podcast media (p = 0.003) and the group given video intervention also showed an increase (13.93 ± 2, 07) with p-value = 0.007. It was found that there were differences in the use of Podcast media and video  on adolescent knowledge about general guidelines for balanced nutrition (p = 0.007).Conclusion : Podcasts and videos affect increasing knowledge level about general guidelines for balanced nutrition in adolescents. Keywords : Adolescents; balanced nutrition guidelines; podcast; spotify; video